Penerapan Iptek Mesin Proses Pembentuk Beras Singkong Pada Usaha Kecil Di Desa Rasau Jaya - Agus Rohermanto Agus Rohermanto; Masril Masril; Rusdaniyar Rusdaniyar; Maryono Efendi; Jaini Jaini (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
The target of this service activity is a small business of cassava rice production in Rasau Jaya Dua Village, Rasau Jaya District, Kubu Raya Regency. The problem partners face is improving the quality and quantity of cassava rice production. The production process still uses simple and manual equipment. The service implementation team and partners are looking for solutions to overcome these problems. From the discussion results, the effort will be made to make quality cassava rice products and increase production capacity to add selling value. The solution offered is to improve the production process so that the product is quality and acceptable to the market. Therefore, it is necessary to apply appropriate science and technology in the form of cassava rice forming process machines and drying machines. Using cassava rice forming and drying machines can improve production more effectively and efficiently, resulting in significant and high-quality production capacity. The result of implementing this service activity is that partners get grants for cassava rice forming process machines and drying machines. From the use of appropriate technology, partner income increased by fifty per cent